Social Interaction of Transvestites in Bireuen Regency - Cut Khairani; Rahmad; Fitri Ernalis; Iqa Nauli; Anjasmara (Britain International for Academic Research (BIAR) Publisher, 2021)
The purpose of the study was to understand the social phenomenon of negative stigma and social exclusion of the existence of transvestite makeup artists through social interaction with the community in Bireuen Regency. This research uses grounded theory with data processing procedure using open coding techniques, coding a stunt and selective coding against data collected through observation, and in-depth interviews. The sample of respondents reached 20 people determined through snowball sampling techniques. The results showed that 53% of makeup artists in Bireuen Regency are transvestites who have experienced a gender identity crisis triggered by imitation actions. This form of social interaction then gets a community response in the form of dissociation, conflict with religious and socio-cultural values that develop in society. Social interaction of cultural accommodation efforts and social structures by transvestite makeup artists was not able to fuse the barriers of negative stigma attached to transgender people in Bireuen Regency.